Wild genotypes of Carica papaya as a strategic resource for product diversification and agro-industrial competitiveness: a genetic, bioactive and agronomic approach (Agroindustria, Sociedad y Ambiente, 2026)
Wild genotypes of Carica papaya have great potential to diversify products and enhance competitiveness in the agroindustry. This research focuses on the genetic diversity, bioactive compounds, and agricultural practices of these genotypes and how they can contribute to the growth of the food industry. A review of 14 relevant scientific articles was conducted and organized through a qualitative analysis. The results show that wild populations exhibit greater genetic diversity than commercial cultivars, making them a key resource for breeding programs aimed at increasing yield, fruit quality, and resistance to diverse conditions. In addition, a high concentration of bioactive compounds—such as carotenoids, flavonoids, vitamins, and enzymes—was identified in different parts of the plant, creating opportunities for the food, pharmaceutical, and cosmetic industries. The study also highlights the use of advanced biotechnological tools, such as genomic selection and genetic editing, to exploit these resources and support more sustainable agricultural practices. The valorization of agro-industrial by-products is considered an important component of circular economy strategies. In conclusion, integrating wild genotypes into productive chains and innovation programs can promote more sustainable development and improve competitiveness in the papaya industry.
Keywords: Carica papaya, wild genotypes, genetic diversity, agro-industry and bioactive compounds